SUPRATROCHLEAR FORAMEN OF THE HUMERUS: MORPHOLOGICAL AND MORPHOMETRIC CHARACTERIZATION IN A BRAZILIAN OSTEOLOGICAL SAMPLE AND CLINICAL IMPLICATIONS - Lucas Gabriel Mota Sousa; Leonardo Barbosa Eliodoro Fernandes; Adryel Assunção Ramalho Leite; José Aderval Aragão (Brazilian Journal of Implantology and Health Sciences, 2026)
ABSTRACT Introduction: The supratrochlear foramen (STF) of the humerus is an anatomical variation characterized by communication between the coronoid and olecranon fossae through the supratrochlear septum. Its identification is of anatomical, radiological, and orthopedic relevance, particularly for image interpretation and the planning of procedures involving the distal end of the humerus. Objective: To determine the frequency of the STF and characterize its morphological patterns and morphometric parameters in dry human humeri. Materials and Methods: This observational, descriptive, and quantitative anatomical study was conducted on 62 dry adult human humeri, comprising 35 left and 27 right specimens. The foramina were morphologically classified as oval, round, irregular, or double. Horizontal and vertical diameters and foramen area were digitally measured using ImageJ® software. Results: The STF was identified in 19 of 62 humeri (30.64%), including 11 left and eight right specimens. The oval morphology was the most prevalent, followed by the round, double, and irregular types. In right humeri, the mean vertical diameter, horizontal diameter, and area were 0.374 cm, 0.495 cm, and 0.187 cm², respectively; in left humeri, the corresponding values were 0.458 cm, 0.605 cm, and 0.242 cm². The horizontal diameter was greater than the vertical diameter on both sides. Conclusion: The STF showed a high frequency and considerable morphological and morphometric variability. Recognition of this anatomical variation is relevant for the differential interpretation of radiolucent findings and for planning orthopedic procedures and intramedullary fixation involving the distal humerus.